Two Compound Heterozygous Variants in SNX14 Cause Stereotypies and Dystonia in Autosomal Recessive Spinocerebellar Ataxia 20 - Maia, Nuno; Soares, Gabriela; Silva, Cecília; Marques, Isabel; Rodrigues, Bárbara; Santos, Rosário; Melo-Pires, Manuel; de Brouwer, Arjan PM; Temudo, Teresa; Jorge, Paula (Frontiers in genetics, 2020)
Autosomal Recessive Spinocerebellar Ataxia 20, SCAR20, is a rare condition characterized by intellectual disability, lack of speech, ataxia, coarse facies and macrocephaly, caused by SNX14 variants. While all cases described are due to homozygous variants that generally result in loss of protein, so far there are no other cases of reported compound heterozygous variants. Here we describe the first non-consanguineous SCAR20 family, the second Portuguese, with two siblings presenting similar clinical features caused by compound heterozygous SNX14 variants: NM_001350532.1:c.1195C>T, p.(Arg399*) combined with a novel complex genomic rearrangement. Quantitative PCR (Q-PCR), long-range PCR and sequencing was used to elucidate the region and mechanisms involved in the latter: two deletions, an inversion and an AG insertion: NM_001350532.1:c.[612+3028_698-2759del;698-2758_698-516inv;698-515_1171+1366delinsAG]. In silico analyses of these variants are in agreement with causality, enabling a genotype-phenotype correlation in both patients. Clinical phenotype includes dystonia and stereotypies never associated with SCAR20. Overall, this study allowed to extend the knowledge of the phenotypic and mutational spectrum of SCAR20, and to validate the role of Sorting nexin-14 in a well-defined neurodevelopmental syndrome, which can lead to cognitive impairment. We also highlight the value of an accurate clinical evaluation and deep phenotyping to disclose the molecular defect underlying highly heterogeneous condition such as intellectual disability.Autosomal Recessive Spinocerebellar Ataxia 20, SCAR20, is a rare condition characterized by intellectual disability, lack of speech, ataxia, coarse facies and macrocephaly, caused by SNX14 variants. While all cases described are due to homozygous variants that generally result in loss of protein, so far there are no other cases of reported compound heterozygous variants. Here we describe the first non-consanguineous SCAR20 family, the second Portuguese, with two siblings presenting similar clinical features caused by compound heterozygous SNX14 variants: NM_001350532.1:c.1195C>T, p.(Arg399*) combined with a novel complex genomic rearrangement. Quantitative PCR (Q-PCR), long-range PCR and sequencing was used to elucidate the region and mechanisms involved in the latter: two deletions, an inversion and an AG insertion: NM_001350532.1:c.[612+3028_698-2759del;698-2758_698-516inv;698-515_1171+1366delinsAG]. In silico analyses of these variants are in agreement with causality, enabling a genotype-phenotype correlation in both patients. Clinical phenotype includes dystonia and stereotypies never associated with SCAR20. Overall, this study allowed to extend the knowledge of the phenotypic and mutational spectrum of SCAR20, and to validate the role of Sorting nexin-14 in a well-defined neurodevelopmental syndrome, which can lead to cognitive impairment. We also highlight the value of an accurate clinical evaluation and deep phenotyping to disclose the molecular defect underlying highly heterogeneous condition such as intellectual disability.